2018
DOI: 10.3389/fnins.2018.00238
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dopamine Neurotransmitter Dynamics and the Blood-Oxygen-Level-Dependent (BOLD) Signal: A Review of Pharmacological Functional Magnetic Resonance Imaging

Abstract: Functional magnetic resonance imaging (fMRI) is widely used in investigations of normal cognition and brain disease and in various clinical applications. Pharmacological fMRI (pharma-fMRI) is a relatively new application, which is being used to elucidate the effects and mechanisms of pharmacological modulation of brain activity. Characterizing the effects of neuropharmacological agents on regional brain activity using fMRI is challenging because drugs modulate neuronal function in a wide variety of ways, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…Also, the observed memory effects might stem from interactions with other neurotransmitter systems (especially noradrenaline [23]) and be tightly linked to specific doses determining the amount of presynaptic vs. postsynaptic blockade [70]. Eventually, additional studies using multi-modal methodological approaches [71] will be necessary to resolve these contradictory drug findings as well to examine the specificity of dopaminergic effects on memory retrieval in more detail.…”
Section: Limitationsmentioning
confidence: 99%
“…Also, the observed memory effects might stem from interactions with other neurotransmitter systems (especially noradrenaline [23]) and be tightly linked to specific doses determining the amount of presynaptic vs. postsynaptic blockade [70]. Eventually, additional studies using multi-modal methodological approaches [71] will be necessary to resolve these contradictory drug findings as well to examine the specificity of dopaminergic effects on memory retrieval in more detail.…”
Section: Limitationsmentioning
confidence: 99%
“…The inside/outside counterparts indicate causalities. Here, each HTB circuit comprising comorbid-like pro les is different from the 19 other circuits identi ed from BOLD activated areas related to pathogenesis, therapy, and pharmacology for single diseases [17][18][19][20][21][22][23][24][25][26][27][28][29]. FS is widely used as a behavioral paradigm to assess depressive behaviors [52], but hypomotility has been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent fMRI studies have highlighted that changes in dopamine signaling can modulate the hemodynamic response in healthy individuals (Alavash et al, 2018;Bruinsma et al, 2018;Guitart-Masip et al, 2016). A number of recent fMRI studies have highlighted that changes in dopamine signaling can modulate the hemodynamic response in healthy individuals (Alavash et al, 2018;Bruinsma et al, 2018;Guitart-Masip et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gamma-aminobutyric acid (GABA) released from interneurons may also act directly on astrocytes or blood vessels and cause vasodilation through GABA-A receptor-mediated effects (Kocharyan, Fernandes, Tong, Vaucher, & Hamel, 2008). We recently reported that CD is associated with an increased availability of GABA-A receptors in the primary motor cortex (Berman et al, 2018) (Alavash et al, 2018;Bruinsma et al, 2018;Guitart-Masip et al, 2016). In individuals with focal hand and laryngeal dystonia, performance of motor tasks involving muscles both affected and unaffected by dystonia was found to be associated with abnormal striatal dopaminergic neurotransmission .…”
Section: Discussionmentioning
confidence: 99%